A review of nonpharmacological strategies in the treatment of relative energy deficiency in sport - Kuikman, M. A.; Mountjoy, M.; Stellingwerff, T.; Burr, J. F. (International Journal of Sport Nutrition and Exercise Metabolism, 2021)
Relative energy deficiency in sport (RED-S) can result in negative health and performance outcomes in both male and female athletes. The underlying etiology of RED-S is low energy availability (LEA), which occurs when there is insufficient dietary energy intake to meet exercise energy expenditure, corrected for fat-free mass, leaving inadequate energy available to ensure homeostasis and adequate energy turnover (optimize normal bodily functions to positively impact health), but also optimizing recovery, training adaptations, and performance. As such, treatment of RED-S involves increasing energy intake and/or decreasing exercise energy expenditure to address the underlying LEA. Clinically, however, the time burden and methodological errors associated with the quantification of energy intake, exercise energy expenditure, and fat-free mass to assess energy availability in free-living conditions make it difficult for the practitioner to implement in everyday practice. Furthermore, interpretation is complicated by the lack of validated energy availability thresholds, which can result in compromised health and performance outcomes in male and female athletes across various stages of maturation, ethnic races, and different types of sports. This narrative review focuses on pragmatic nonpharmacological strategies in the treatment of RED-S, featuring factors such as low carbohydrate availability, within-day prolonged periods of LEA, insufficient intake of bone-building nutrients, lack of mechanical bone stress, and/or psychogenic stress. This includes the implementation of strategies that address exacerbating factors of LEA, as well as novel treatment methods and underlying mechanisms of action, while highlighting areas of further research.